Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Efficient and mild method for preparation of allylic amines from aziridine-2-alcohols using PPh3/I-2/imidazole - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N. (Tetrahedron Letters, 2014)
Allylic amines are synthesized in good to excellent yields by treatment of aziridine-2-alcohols with PPh3/I-2/imidazole in THF as solvent under mild conditions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chiral allylic amine; Chiral aziridine-2-alcohols; PPh3/iodine/imidazole; Reductive elimination

Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Short enantioselective total synthesis of (R)- and (S)-pipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Kalbhor, Dinesh B. (Tetrahedron-Asymmetry, 2014)
A convenient and practical total synthesis of (R)- and (S)-pipecolic acid has been achieved by utilizing chiral cis-aziridine-2-carboxylate as the common synthetic precursor. The synthesis involves regioselective reductive cleavage of the aziridine ring and Wittig olefination as key reactions. (C) 2014 Elsevier Ltd. All rights reserved.

Stereospecific synthetic approach towards tamiflu using the ramberg-backlund reaction from cysteine hydrochloride - Chavan, Subhash P.; Chavan, Prakash N.; Gonnade, Rajesh G. (RSC Advances, 2014)
The stereospecific formal synthesis of Tamiflu from L-cysteine hydrochloride as the chiral source is described. The notable feature of the present strategy is the Ramberg-Backlund reaction and Sharpless-Reich protocol as the key chemical transformations to access the cyclohexene skeleton of Tamiflu.

Enantioselective syntheses of (R)-pipecolic acid, (2R,3R)-3-hydroxypipecolic acid, beta-(+)-conhydrine and (-)-swainsonine using an aziridine derived common chiral synthon - Chavan, Subhash P.; Khairnar, Lalit B.; Pawar, Kailash P.; Chavan, Prakash N.; Kawale, Sanket A. (RSC Advances, 2015)
Concise total syntheses of (R)-pipecolic acid, (R)-ethyl-6-oxopipecolate, (2R, 3R)-3-hydroxypipecolic acid and formal syntheses of beta-(+)-conhydrine, (-)-lentiginosine, (-)-swainsonine and 1,2-di-epi-swainsonine have been accomplished starting from a common chiral synthon. The present strategy employs regioselective aziridine ring opening, Wittig olefination and RCM as the key chemical transformations.

Asymmetric total synthesis of L-allo-1-deoxynojirimycin - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P.; Chavan, Prakash N.; Khairnar, Lalit B. (Arkivoc, 2016)
Asymmetric total synthesis of L-allo-1-deoxynojirimycin (L-allo-DNJ) was achieved from cis-butene-1,4-diol by employing Sharpless asymmetric dihydroxylation, stereoselective flash dihydroxylation and ring enlargement reactions as key steps.
Keywords: diastereoselective flash dihydroxylation; ring-enlargement reaction; sharpless asymmetric dihydroxylation

Formal synthesis of brivaracetam: a key to construct the pyrrolidone scaffold using Pd-catalyzed oxidative cyclization and ring-closing metathesis reaction - Chavan, Subhash P.; Kawale, Sanket A.; Chavan, Prakash N. (Tetrahedron Letters, 2019)
A short and efficient synthetic approach for brivaracetam has been accomplished via two different routes which utilize Pd-catalyzed oxidative cyclization and ring-closing metathesis (RCM) as the key reaction. These two routes are novel, simple, scalable and rely on (E)-pent-2-en-1-ol and valeraldehyde as a commercially available starting material to yield brivaracetam with good overall yield. (C) 2019 Published by Elsevier Ltd.
Keywords: Antiepileptic drugs; Pd-catalyzed oxidative cyclization; pyrrolinone; Ring-closing metathesis reaction

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)